Echinoagave nievesiorum (Agavaceae, Asparagales): A new species from the Sierra Madre Occidental, Jalisco, Mexico - Vázquez-García, J. Antonio; Nuño-Rubio, Ana T.; García-Morales, Leccinum Jesús; Lomelí-Hernández, Juan Luis; Cházaro-Basáñez, Miguel. J.; Padilla-Lepe, Jesús; Cristóbal-Gabriel, Saúl; Hernández-Vera, Gerardo; Muñiz-Castro, Miguel Á. (Phytotaxa, 2024)
Echinoagave nievesiorum (Agavaceae, Asparagales), a new species endemic to the Sierra Wixárika (Huichola), part of the Sierra Madre Occidental, Jalisco, Mexico, is described. This species shares morphological characteristics with Echinoagave rzedowskiana but it differs from the latter by having narrower and striate leaves; leaf sheaths shorter, triangular and wider at the base; narrower ovary width; shorter tube length; tepal lobes at anthesis converging and tightening the filaments; larger filament length to flower length ratio; fruiting spikes thicker and denser with the peduncle covered by the capsules and the bracts usually deciduous; capsules broadly ellipsoid with dorsally blackish valves. A distribution map with biogeographic provinces is provided to place the species in an ecological and evolutionary context.